Lactobacillus plantarum G1 microencapsulation enhanced its viability during storage and gastrointestinal transit - Ouled-Haddar, Houria; Sifour, Mohamed; Idoui, Tayeb; Bouridane, Hamida; Arid, Somia (Penerbit Universiti Kebangsaan Malaysia, 2016)
A Lactobacillus plantarum strain G1 was previously isolated from chicken crop and it was found to show interesting probiotic properties. In this study, several microencapsulation combined materials were used to test their ability to protect cells from gastrointestinal harsh conditions. The results on kinetics of cell release after exposition to acidic pH (2.0) indicated that the efficiency of cell entrapment of the gels was as follows starting from the highest capacity to the lowest one: sodium alginate, alginate-agar (AA), alginate-starch (AS) and κ-carrageenan. In addition, effect of bile salts on cell release was also tested; the results showed that the efficiency of entrapment of the gels was different and as follows starting from the highest capacity to the lowest one: AA, sodium alginate, κ-carrageenan, and AS. Moreover, viability of free and alginate-microencapsulated Lactobacillus plantarum after exposure to acid, bile and pancreatic enzymes was investigated; the results showed that microencapsulation was capable of protecting cells against the harsh conditions of the gastrointestinal tract. In addition, microencapsulation enhanced the viability of Lb. plantarum during cold storage for 2 weeks and during a range of heat treatments.